An Annotated List of Auchenorrhyncha and Heteroptera Collected in the Coastal Salt Marshes of the Mississippi Delta in Louisiana - I. M. Sokolov; X. Chen; R. M. Strecker; L. M. Hooper-Bùi (Psyche: A Journal of Entomology)
Insects that live in the saltwater and brackish marshes, which fringe the northern coast of the Gulf of Mexico, are largely unstudied. During 2011–2013, a survey of insect fauna of the coastal salt marshes of the Mississippi Delta in Louisiana was conducted. We present the species of terrestrial representatives of Heteroptera and Auchenorrhyncha collected during that study. The Auchenorrhyncha are represented by 33 species in 6 families, with Cicadellidae (16 species) and Delphacidae (13 spp.), and are the most diverse. The terrestrial heteropterans are represented by 11 species in 5 families with the majority of species in Miridae (6 spp.). A list of species, annotated with numbers of specimens collected, ranges of collection dates (seasonality), and published information on their hosts, habitats, and ranges, is presented. Of 44 identified species, ten species (22.7%) are reported from Louisiana for the first time. The paper provides evidence of a diverse terrestrial arthropod community in brackish marshes; a community that is largely understudied.